Improvement of Elderly Welfare Through Food Program - Nur, Muhammad Sofyan; Mursyidah, Lailul (Indonesian Journal of Cultural and Community Development, 2025)
The general background increasing number of elderly in society requires effective welfare programs to meet their specific needs. Specific background in Indonesia, the Food Program of the Ministry of Social Affairs aims to provide essential nutritional support for this demographic group. Knowledge gap although this program has been implemented, there is still a lack of comprehensive analysis regarding its effectiveness and reach, especially in the Sidoarjo District. This study aims to fill this knowledge gap by evaluating the program through descriptive qualitative methods, including observation and interviews. Results findings indicate that the implementers' understanding of the program has improved due to socialization activities. Positive changes have been recorded among beneficiaries, demonstrating the program's potential to improve the welfare of the elderly. The novelty of this study lies in the comprehensive assessment of the components of the Food Program. Implications these findings can serve as a guide for improving and adapting social welfare programs in the future, emphasizing the importance of addressing the welfare of the elderly in community development initiatives. Highlights: Improved understanding of the Food Program through socialization activities. Need to increase the number of eligible elderly beneficiaries. Program meets health standards, indicating successful food provision. Keywords: Program, Food, Social, Effectiveness, Welfare